Damage mechanism of crown spring for the EMU traction Motor's connector. (August 2022) - Wang, He; Liu, Jianhua; He, Jifan; Ren, Yanping; Peng, Jinfang; Zhu, Minhao
Highlights: The failure analysis of in-service electrical connector is carried out, which has reference value for engineering practice. The current-carrying wear of the reeds in the crown springs were studied. From the macro and micro point of view, the state of the crown springs in each damage stage is described in detail. The process of the crown spring in actual use from brand new to severely burned in real service is explained in detail. Abstract: The electrical connector of the traction motor is an important device to ensure the stable operation of the electronic system of the EMU. Damage to the crown spring inside the connector will cause the traction motor to lose power supply. In this work, the damage morphology, composition and damage depth of the crown spring damage area were systematically analyzed using macroscopic and microscopic analysis equipment. Results show that the coating of the slightly damaged reeds was oxidized. Moderately damaged reeds have severe mechanical wear that caused the coating to disappear. Severely damaged reeds are caused by the combined action of mechanical wear, electrical wear and oxidative wear. At this stage, the connector joint heats up rapidly, which causes the crown spring to melt. The results show that the failure of the crown spring is the result of the combined effect of mechanical wear, electrical wear, and oxidative wear.